Studi Literatur: Pengembangan Biogasoline dengan Pemanfaatan Arak Bali Sebagai Bahan Bakar Kendaraan Ramah Lingkungan - Komang Purnayasa; Ngurah Putu Putra Adnyana; I Gede Wiratmaja (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
The use of biogasoline from Bali wine as a fuel additive in gasoline from fossil energy sources gets a lot of severe problems, especially to make biogasoline products as an alternative fuel that is able to stand alone as the main fuel in Indonesia in the future. This article is in the making based on the results of literature studies by conducting an analysis process on various sources of pre-existing articles. This literature study is processed in various ways such as reviewing the results of previous research on the use of Balinese wine as one of the energy-friendly fossil fuel substitutes. From this literature study obtained the advantages of an engine working umjuk, namely the use of biogasoline from Balinese wine to variations in compression ratio the greater the acceleration produced is also increasing which makes the combustion of the table better, and also the use of fuel becomes more efficient. The use of biogasoline fuel additives from Bali wine against exhaust emissions in the form of carbon monoxide (CO) and carbon dioxide (CO₂) gases decreased. Then in terms of raw materials, it is feared that there is competition between the availability of food raw materials (the manufacture of brown sugar and ant sugar). One solution so that ethanol from Balinese wine in pure biogasoline that can be used as fuel is with adsorbed type treatment and immersion time and interaction are very influential on the quality of biogasoline concentration and percentage value increase in biogasoline concentration when in the dehydration process.